A Case of Fatal Penicillium Rhinosinusitis in a Patient With Acute Myelogenous Leukemia and Prolonged Neutropenia. Issue 6 (November 2018) - Shah, Niel N.; Midha, Shonali; Nanjappa, Sowmya; Greene, John N.
Abstract : Abstract: Because of a rising number of immunocompromised patients, there is an increase in unusual aggressive mold infections. After a pulmonary site of infection, rhinosinusitis is the second most common site. Although the most common agents responsible for invasive fungal rhinosinusitis are species of Aspergillus, Fusarium, the Mucorales, and dematiaceous (brown-black) molds, we report an unusual case of invasive fungal rhinosinusitis caused by Penicillium species in a patient with acute myeloid leukemia with prolonged neutropenia. We present the clinical case, diagnostic modalities, and treatment options of invasive fungal rhinosinusitis. Abstract : The authors describe a case of invasive Penicillium sinusitis infection in a patient with acute myelogenous leukemia and prolonged neutropenia along with diagnostic modalities and treatment options of invasive fungal rhinosinusitis.